Pseudorabies virus infection of the rat central nervous system: ultrastructural characterization of viral replication, transport, and pathogenesis - Card, JP (J Neurosci, 1993)
Pseudorabies virus (PRV) has been used extensively to map synaptic circuits in the CNS and PNS. A fundamental assumption of these studies is that the virus replicates within synaptically linked populations of neurons and does not spread through the extracellular space or by cell- to-cell fusion. In the present analysis we have used electron microscopy to characterize pathways of viral replication and egress that lead to transneuronal infection of neurons, and to document the non-neuronal response to neuronal infection. Three strains of PRV that differ in virulence were used to infect preganglionic motor neurons in the dorsal motor nucleus of the vagus (DMV). The data demonstrate that viral replication and transneuronal passage occur in a stepwise fashion that utilizes existing cellular processes, and that the non-neuronal response to infection serves to restrict nonspecific spread of virus by isolating severely infected neurons. Specifically, capsids containing viral DNA replicate in the cell nucleus, traverse the endoplasmic reticulum to gain access to the cytoplasm, and acquire a bilaminar membrane envelope from the trans cisternae of the Golgi. The outer leaf of this envelope fuses with the neuron membrane to release virus adjacent to axon terminals that synapse upon the infected cell. A second fusion event involving the viral envelope and the afferent terminal releases the naked capsid into the bouton. Systematic analysis of serial sections demonstrated that release of virus from infected neurons occurs preferentially at sites of afferent contact. Nonspecific diffusion of virus from even the most severely infected cells is restricted by astrocytes and other non-neuronal elements that are mobilized to the site of viral infectivity. The ability of glia and macrophages to restrict spread of virus from necrotic neurons is the product of (1) temporal differences in the mobilization of these cells to the site of infection, (2) differential susceptibility of these cells to PRV infection, and (3) abortive viral replication in cells that are permissive for infection. The findings provide further insight into the intracellular routes of viral assembly and egress and support the contention that transneuronal spread of virus in the brain results from specific passage of virions through synaptically linked neurons rather than through cell fusion or release of virus into the extracellular space.